2022
DOI: 10.1155/2022/8083443
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanism and Acoustic Emission Precursors of Coal Samples considering Bedding Effect under Triaxial Unloading Condition

Abstract: Bedding increases coal seam anisotropy, which leads to significant differences in the evolution laws of mining stress and strata movement. This work analyzed the dip angles of different layers to analyze the mechanical properties of the coal seam under unloading. The coal sample was subjected to triaxial compression and unloading damage acoustic emission testing. The brittleness characteristics of the coal sample failure in different bedding directions differed significantly. Compared with axial parallel beddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Assuming that the AE equivalent magnitude meets the past law, by taking the parameter "N" as 1 in Equation ( 5), the "maximum magnitude" at coal specimen failure can be predicted according to the following equation: b a M = max (7) where Mmax is the predicted "maximum magnitude" at the coal specimen failure.…”
Section: Prediction Of Ae Maximum Magnitudementioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that the AE equivalent magnitude meets the past law, by taking the parameter "N" as 1 in Equation ( 5), the "maximum magnitude" at coal specimen failure can be predicted according to the following equation: b a M = max (7) where Mmax is the predicted "maximum magnitude" at the coal specimen failure.…”
Section: Prediction Of Ae Maximum Magnitudementioning
confidence: 99%
“…So, it is very significant to study the damage and failure evolution characteristics of coal specimens subjected to graded uniaxial cyclic loading and unloading for coal mine production safety. Many studies have shown that the rock produces acoustic emission (AE) phenomenon under the loading [7][8][9][10]. Some studies have also shown there exist the Kaiser and Felicity effects in the AE phenomenon [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [15] established a model for the calculation of anisotropic coal permeability and analyzed the distribution pattern of permeability in arbitrary directions at different angles to the beds plane. Li et al [16][17][18] investigated the effect of circumferential pressure and bedding angle on the mechanical properties of coal. Liu et al [19,20] carried out LNMR and NMR studies of the microstructural characteristics and pore size distribution of high-grade coals with different bedding structures.…”
Section: Introductionmentioning
confidence: 99%